2016
DOI: 10.1111/cch.12356
|View full text |Cite
|
Sign up to set email alerts
|

Parent‐related mechanisms underlying the social gradient of childhood overweight and obesity: a systematic review

Abstract: Families from different SES groups have different risk and protective factors for COWOB. Prevention and intervention efforts may have improved efficacy if they are tailored to address specific risk factors within SES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 66 publications
(128 reference statements)
3
53
1
1
Order By: Relevance
“…In younger children direct involvement of parents is a key factor for success [22][23][24]. While obesity tends to run in families [25][26][27] and parents remain an important influence for adolescents [28], the importance of peers and increasing autonomy make it difficult to know how best to engage parents in adolescent weight management programs. To date, research findings have been mixed regarding the extent to which involving parents is beneficial for adolescent weight loss [29].Al-Khudairy et al found that behavioral interventions for adolescents that involved parents, compared to those with no parental involvement, did not seem to differ in effectiveness for weight-related outcomes [30].…”
Section: Introductionmentioning
confidence: 99%
“…In younger children direct involvement of parents is a key factor for success [22][23][24]. While obesity tends to run in families [25][26][27] and parents remain an important influence for adolescents [28], the importance of peers and increasing autonomy make it difficult to know how best to engage parents in adolescent weight management programs. To date, research findings have been mixed regarding the extent to which involving parents is beneficial for adolescent weight loss [29].Al-Khudairy et al found that behavioral interventions for adolescents that involved parents, compared to those with no parental involvement, did not seem to differ in effectiveness for weight-related outcomes [30].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst these interventions are important and have the potential to play a part in an overarching anti-obesity strategy, children can develop a tendency towards overweight and obesity before they reach school age (Mech, Hooley, Skouteris, & Williams, 2016; Ventura & Birch, 2008), with parental practices in relation to food having an effect on this trajectory (Golan, Weizman, Apter, & Fainaru, 1998; Heinberg et al, 2010; Spruijt-Metz, Lindquist, Birch, Fisher, & Goran, 2002; Ventura & Birch, 2008). However, studies reporting on interventions for treating obesity in children may produce results which cannot be generalized to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of research on the topic has centered around a frequently discussed and uneven distribution of overweight across ethnicities in many countries [3,8,23]. However, our study identified another factor that contributes to overweight adolescents in Chinese cities like Shanghai with high rates of immigration from other less-developed areas; a system that limits access to equal educational resources.…”
Section: Discussionmentioning
confidence: 72%
“…This development has attracted a growing concern from both the government and the public. A growing body of research indicates that the causes of adolescent obesity involves a variety of factors, including children’s personal characteristics (e.g., age, gender, ethnicity), maternal healthy behaviors (i.e., breastfeeding, maternal smoking behavior), children’s physical activity and sedentary behaviours, diet (i.e., food nutrition, food access), family socioeconomic position (e.g., parents’ education, income and occupation), and school environment [1,2,3,4,5,6,7,8,9,10,11,12]. …”
Section: Introductionmentioning
confidence: 99%